(3QSGdI Mj Hf jbXGfs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI hGdOjHGLI hbO JjSQJ hGdJjSjQ ef GdMVQI LdJ fgVI hGHJYGK HbhGA GdeSJNOeI ai GdeGOI ddJYbd Yf MGdI eG cfJ HUOOg s
(3BNQgG (B:s
(3Ke bGd Mj Hf jbXGf dhdG Cf JTHgc Ydi gPg GdMbGFb eeG jVQHfj Edi Jdc GdTOI hjOfjfj Rdaj Edi Jdc GdMVQI hGdEdcGf dj Hg TYd TGZd Yfc s
(3Vef eLehY , JQJjHgG (B: 7s
(3GdfSNI HgG MhGTs
Keywords: (3eJaQbGJs